Synthesis of 2`-hydroxy-4`-isoprenyloxychalcone Derivatives with Potential Antidepressant-like Activity - Xie, Chao; Peng, Zhou; Zhao, Shui-Lian; Pan, Cheng-Yan; Guan, Li-Ping; Sun, Xian-Yu (Medicinal Chemistry, 2014)
A series of 2´-hydroxy-4´-isoprenyloxychalcone derivatives was synthesized and evaluated for its antidepressant- like activity using the FST and TST. All compounds exhibited the potential antidepressant-like activity in the FST and the TST through intraperitoneal injection. Among them, compounds 4i, 4l and 4n exhibited more potent antidepressant- like activity at a dose of 10 mg/kg. And, compounds 4i, 4l and 4n were also adequately absorbed in mice after oral administration at a dose of 30 mg/kg. In the 5-HT induced head-twitch test and yohimbine induced mortality test, compound 4i could increase the head-twitch and rise mortality in mice. The results suggested that the antidepressant effects of compound 4i may be related to via the serotonergic and noradrenergic system.
Keywords: synthesis